Efficacy of antimicrobial compounds against Salmonella spp., Escherichia coli O157:H7, non-O157 Escherichia coli, and non-pathogenic Escherichia coli on beef and poultry - Scott, Brittney R., author; Delmore, Robert J., advisor; Belk, Keith E., advisor; Woerner, Dale R., committee member; Bunning, Marisa, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Keywords: beef; non-O157 STEC; Escherichia coli O157:H7; antimicrobial; poultry; Salmonella